Optimizing Production of Kwh Legon PLTD PLTD Using Wind Turbine Generator Model B. Ventus 250 KW(Case Study on Karimunjawa Island) - Safrizal, Safrizal; Sutikno, Ery; Arifin, Zaenal (Fakultas Teknik Universitas 17 Agustus 1945 Cirebon, 2023)
Electricity supply must be able to reach all users, including those on small islands in Indonesia, one of which is Karimunjawa Island. Starting in 2016 Karimunjawa Island is supplied by 2 units of Legon Bajak Diesel Power Plant (PLTD) with a capacity of 2x2.2 MW. Based on the peak electricity demand on Karimunjawa Island, each month from January 2017 to December 2018 increased by about 3.9% with an hourly peak load of 1,146 kWh. The average consumption of PLTD Legon Bajak every month in 2018 is 194,877 liters / month. The higher the kWh production of a PLTD, the higher the operational costs for fuel. In addition to the high price of fuel, combustion results from PLTD operations also cause air pollution. Based on these problems in this study will analyze the optimization of the kWh Legon Bajak PLTD using a wind turbine generator model b.ventus 250 kW of 3 units with an assumption of 50% of the peak load, because on Karimunjawa Island has a high enough wind energy potential. The average wind speed from 2004 to 2015 in several areas of Karimunjawa Island was 5.7 m / s. In this study will calculate technical analysis and economic analysis. In the technical analysis the wind turbine generator power output is calculated using the weibull method based on wind speed and power curve b.ventus 250 kW while the economic analysis calculates the cost of fuel savings that can be achieved after optimization calculations. Calculation results show wind turbine power output of 990,981 kWh / year. Based on the specific value of fuel consumption (SFC) of 0.432 liters / kWh fuel consumption during 2017 amounted to 1,605,453.9 liters / year while for 2018 it was 2,338,528.1 liters / year. From the 3 wind turbine electricity supply of 2,972,943 kWh / year, it will reduce fuel consumption by 1,284,311.4 liters / year with a saving cost of Rp.15,989,291,338.00. The amount of optimization of the kWh PLTD after the supply of 3 units of b.ventus 250 kW wind turbine model in 2017 was 80% while in 2018 it was 54.9%.